SO(2N) and SU(N) gauge theories in 2+1 dimensions - Bursa, F; Lau, R; Teper, M (2013)
We perform an exploratory investigation of how rapidly the physics of SO(2N) gauge theories approaches its N = ∞ limit. This question has recently become topical because SO(2N) gauge theories are orbifold equivalent to SU(N) gauge theories, but do not have a finite chemical potential sign problem. It is therefore interesting to know how close is the physics of SO(N) to that of SU(3) for the modest values of N where one might be able to perform chemical potential calculations. We consider only the pure gauge theory and, because of the inconvenient location of the lattice strong-to-weak coupling 'bulk' transition in 3 + 1 dimensions, we largely confine our numerical calculations to 2 + 1 dimensions in this paper. We provide some analytic estimates of the SO(2N) spectrum in both D = 2 + 1 and D = 3 + 1, and show, numerically, that the D = 2 + 1 SO(6) and SU(4) low-lying spectra do indeed appear to be the same. Our numerical calculations of a number of mass ratios show that the leading O(1/N) correction already dominates for N ≥ 6, and in some cases down to N = 4, and that, as expected, these ratios become consistent with those of SU(N) as N → ∞. In particular we see that SO(6) and SU(3) gauge theories are quite similar except for the values of the string tension and coupling, both of which differences can be readily understood. © 2013 SISSA, Trieste, Italy.